Immobilization of glutaminase enzyme from Hypocria jecorina on polyacrylic acid: preparation and biochemical characterization - Karahan, Mesut; Karakus, Emine; Bulbul, Dilara; Ataci, Nese (TAYLOR & FRANCIS LTD, 2014)
L-glutaminase enzyme produced from Hypocrea jecorina pure culture and polyacrylic acid (PAA) in the presence Cu2+ ions were composed the ternary complex at pH 7. The properties of free and immobilized enzyme were defined. The effect of various factors such as pH, temperature, heat, and storage stability on immobilized enzyme were investigated. The properties of immobilized enzyme were investigated and compared to those of free enzyme. Optimum pH and temperature of both enzyme were determined to be 8.0 and 50 degrees C, respectively. Kinetic parameters of the immobilized enzyme (Km and Vmax values) were also determined as 0.38 mM of the Km and 10.9 U/L of the Vmax. No drastic change was observed in the Km and Vmax values. Thermal and storage stability experiments were carried out. The thermal stability studies indicated that the immobilization process tends to stabilize the enzyme.
Keywords: enzyme production; L-Glutaminase enzyme; immobilization; microorganism; polyacrylic acid; ternary metal complexes; COVALENT IMMOBILIZATION; SALT-TOLERANT; AMINO-ACIDS; ASPARAGINASE; BIOSENSOR; SURFACE; OXIDASE; BEADS; Biotechnology & Applied Microbiology; Engineering; Materials Science